Assessment of community disaster resilience the case of flood and landside-prone communities in Buhi, Camarines Sur - Magayanes, Laarni M.; Jago-on, Karen Ann B. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
The Philippines is already used to being affected by numerous natural disasters. Many strong typhoons and other natural disasters have already caused disastrous effects on the lives and properties of the Filipinos. The exposure and susceptibility of the country to natural and human-induced hazards, caused efforts and initiatives to strengthen communities and people's capacities and resilience to disasters.

The study assessed the resilience of communities and households to flooding and landslide hazards using the resilience elements; social, economic, and institutional. The impacts of previous disasters in terms of characteristics were identified to determine community experiences. The mitigation measures and coping mechanisms were identified to determine the current programs, projects, and activities that the government authority has implemented to reduce vulnerabilities and increase capacity to flooding and landslides.

A mixed method of qualitative and quantitative research was employed to answer the study's research questions. For the qualitative research method, key informant interview using a guide question was administered to 4 local and barangay officials while for the quantitative research, a household survey was administered to 123 household respondents using a structured survey questionnaire. Available materials such as municipal and barangay disaster risk reduction and management plans (M/BDRRMP) were reviewed which served as references for cross-validation. The results of the key informant interviews and household surveys were cross-validated to determine a significant association between the results of the key informant interviews and household surveys.

The findings indicate that both barangays have significant results in community disaster resilience factored by social, economic, and institutional resilience dimensions, and a combination of mitigation measures and coping mechanisms. The assessment identified areas that need improvement and key strategies in building community disaster resilience. The results underscore the importance of community disaster resiliency planning. There is also a need to strengthen community participation, advocacy, and public awareness toward increasing understanding of community resilience and disaster risk reduction. Other strategies for consideration are a diversified local economy, establishment of transportation linkages, access to basic services and facilities such as evacuation centers, and proactive local and barangay government.

The study contributes to disaster resilience planning by providing an assessment of the factors affecting community resilience and suggesting evidence-based recommendations for improving resiliency at the community level. Key recommendations include strategies on capacity building, resource allocation, structural and non-structural measures, and inclusive and meaningful participation of all stakeholders.

The researcher concludes that community disaster resilience can be integrated into the development of Local and Barangay Disaster Risk Reduction and Management Plans, Comprehensive Land Use Plans (CLUPs), and Comprehensive Development Plans (CDPs) by including programs and activities for disaster prevention, mitigation, and preparedness.
Thesis
Keywords: Emergency management -- Philippines -- Buhi (Camarines Sur); Public safety -- Philippines -- Buhi (Camarines Sur)